DETERMINAN VARIABEL MAKROEKONOMI TERHADAP PEMBIAYAAN MUDHARABAH PERBANKAN SYARIAH INDONESIA: ANALISIS ERROR CORRECTION MODEL (ECM) - Misfi Laili Rohmi; Mahfudz Reza Fahlevi (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2022)
This study intends to investigate the impact of macroeconomic factors such as inflation, the BI rate, the exchange rate, and the Money Supply (JUB) on Islamic banking's mudharabah financing, which includes all Islamic Commercial Banks (BUS) and Sharia Business Units (UUS) in Indonesia. The Error Correction Model (ECM) analysis was used to identify the short- and long-term effects of the independent variable on the dependent variable. During the monthly period of 2016-2021, secondary data was gathered from Sharia Banking Statistics (SPS) OJK, Central Statistics Agency (BPS), and Bank Indonesia (BI). The data show that only the Money Supply (JUB) has an influence on internal mudharabah financing in the near term, whereas the other three factors, such as inflation, BI rate, and interest rate, have no effect.